1962
DOI: 10.1243/pime_proc_1962_176_050_02
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of the Performance of High-Speed Lightly Loaded Cylindrical Roller Bearings

Abstract: The paper deals with the wear problems which are sometimes experienced when operating parallel cylindrical roller bearings at high speed, with jet lubrication, in turbine mainshaft bearing practice.Tests show that considerable cage slip often takes place, as reported by previous investigators, the cage and roller assembly travelling at speeds lower than that predicted from the epicyclic relationship. I t is concluded that hydrodynamic lubrication normally occurs between the rollers and races when appreciable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1967
1967
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…Unfortunately, this analysis indicated that cage and roller slip was independent of the operating conditions and that the latter (roller slip) was also independent of the roller position in the bearing. This is contrary to actual measurements [1,[8][9][10].…”
Section: Introductioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Unfortunately, this analysis indicated that cage and roller slip was independent of the operating conditions and that the latter (roller slip) was also independent of the roller position in the bearing. This is contrary to actual measurements [1,[8][9][10].…”
Section: Introductioncontrasting
confidence: 76%
“…Not surprisingly, the measurement of roller speed, more than any other variable, has tended to limit the potential of experimental studies to date. The electromagnetic techniques generally employed for this measurement [1,[7][8][9][10] have only been capable of measuring the average speed of a single, modified roller, taken over a number of revolutions, due mainly to the inherent resolution limitations of the method. Typically, Boness [1] spark eroded a slot in the end face of one roller and mounted a small magnetic probe on the cage opposite the roller, the signal from this transducer being transmitted to a stationary receiver by a magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith [20] reported the effect of oil viscosity, diametral clearance and outer race temperature on cage slip. Poplawski [21] analyzed the effects of oil temperature on cage slip.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage is that wear sometimes occurs [12]. For wear to occur there must be both sliding and a breakdown in lubrication.…”
Section: H Oz W T W Cmentioning
confidence: 99%